EFEKTIVITAS BUKU PEMANTAUAN PENCEGAHAN HIPERTENSI TERHADAP PENCEGAHAN HIPERTENSI LANSIA DI RW 04 KELURAHAN LAWANG GINTUNG KOTA BOGOR TAHUN 2022 - Siti Atikah (2022)
Hypertension is known as the silent killer disease, which is a hidden killer disease, because of its high prevalence and level of malignancy that can cause permanent disability and sudden death. The purpose of the study was to analyze the effectiveness of the hypertension prevention monitoring book in RW 04, Lawang Gintung Village, Bogor City in 2022. The type of research used was quantitative with a pre-experimental design (pre-experimental design) one group pretest posttest design. Population 50 elderly people. Sampling using non-probability sampling method with a total sampling of 50 elderly people. Data analysis using univariate analysis and bivariate analysis using Wilcoxon test. The results showed that there were differences in hypertension prevention behavior after being given an intervention in the form of a hypertension prevention monitoring book, namely smoking behavior (p value 0.003), sleeping too late (p value 0.000), physical activity behavior (p value 0.000) and excessive salt consumption (p value 0.000).There is an increase in the behavior of preventing hypertension in the elderly after being given an intervention in the form of a hypertension prevention monitoring book. Keywords: Hypertension Prevention Monitoring Book, Hypertension, Elderly, Hypertension Prevention Behavior